Endoscopic Endonasal Landmarks to the Greater Palatine Canal: A Radiographic Study - Campbell, Raewyn G.; Solares, C. Arturo; Mason, Eric C.; Prevedello, Daniel M.; Carrau, Ricardo L. (Journal of Neurological Surgery Part B: Skull Base, 2018)
Background The palatine neurovascular bundle is at risk during endoscopic surgery. Injury may result in significant blood loss and anesthesia of the ipsilateral hard palate. Nonetheless, its endoscopic anatomy has not been described previously. This article strives to establish landmarks to identify the greater palatine canal; thus, avoiding injury to its contents.Methodology This study comprised 50 deidentified computed tomographic angiograms using landmarks that are immediately visible during endoscopic medial maxillectomy to calculate: the angle of the greater palatine canal to the vertical, the distance from the anteroinferior aspect of the greater palatine canal to the orifice of the nasolacrimal duct, the distance from the anteroinferior aspect of the greater palatine canal to the posterolateral free edge of the hard palate, and the distance from the anterior aspect of the greater palatine canal as it enters the hard palate to the posterior wall of the maxillary sinus.Results The mean angle of the greater palatine canal to the vertical was 23.01 degrees. The mean distance from the anteroinferior aspect of the greater palatine canal to the nasolacrimal duct was 31.52 mm. The mean distance from the anterior aspect of the greater palatine canal to the posterolateral free edge of the hard palate was 7.71 mm and the mean distance from the anterior aspect of the greater palatine canal to the posterior wall of the maxillary sinus was 7.07 mm.Conclusion Accessible anatomical landmarks help ascertain the location of the greater palatine canal intraoperatively; thus, avoiding injury to its contents.
Keywords: anatomy; epistaxis; nasal; sinus; skull base